Research on transnational Yucatec Maya-speakers negotiating multilingual California. Issue 1 (24th August 2015) - Whiteside, Anne
Abstract : This project combined methodologies from linguistic anthropology, participatory action research and interactional sociolinguistics. Data was collected from participant observation, four case studies, extensive interviews and a language and literacy survey. Multilingual conversations were recorded and analyzed with Conversation Analysis, with a focus on actions and identities as they emerge through enacted stance. The analysis was informed by concepts taken from the anthropology and sociology of transnationalism. The study shows four Maya-speaking individuals negotiating highly multilingual social worlds, where English, when it appears, is more often lingua franca than dominant code, and where participants use their various languages strategically and contingently to accomplish their various goals. These choices are constrained by their status as workers at the bottom rung of a social field characterized by undocumented status and the persistence of colonial discourses. Recommendations for research and practice based on research findings: -reconsideration of second language pedagogies for such immigrant populations -the use of stance in the analysis of multilingual conversations -more research on undocumented status and how it contributes to the silencing of minority language populations -the use of participatory research methods in studies of undocumented and indigenous communities